ANALISIS PENERAPAN EVALUASI HASIL BELAJAR SISWA PADA KURIKULUM TINGKAT SATUAN PENDIDIKAN DAN KURIKULUM 2013 DALAM MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH PERTAMA NEGERI 1 KECAMATAN BINJAI KABUPATEN LANGKAT TAHUN AJARAN 2017/ 2018 - Afrah Maulida (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2019)
This study aims to find out: 1)Application of evaluation of studentlearning outcomes on curriculum KTSP in PAI subjects in SMP Negeri 1Binjai District Langkat Regency Teaching Year 2017/2018.2)Implementation of the evaluation of student learning outcomes oncurriculum 2013 in PAI subjects in SMP Negeri 1 Binjai District LangkatRegency Teaching Year 2017/2018. 3) Analysis of the implementation ofthe evaluation of student learning outcomes in the educational unitcurriculum (KTSP) and curriculum 2013 in the subjects of PAI in SMPNegeri 1 Binjai District, Langkat Regency Teachings Year 2017/ 2018.Themethod used in this study is a qualitative methodology by using thedescription approach, while the instrument is the researcher. The datacomes from two sources namely primary and secondary data. Datacollection techniques consist of observation, interview, anddocumentation. The analysis technique used is data reduction, datapresentation, and conclusion. The examination of the validity of the dataof researchers using 4 techniques of degree of trust, transparency,dependence, and certainty with triangulation of sources and datacollection. The result of the research shows that the implementation of theevaluation of student learning outcomes in KTSP and the curriculum 2013in PAI subjects at SMP Negeri 1 Binjai District Langkat District 2017/ 2018academic year is categorized quite well, KTSP is used in class IX, andcurriculum 2013 is used in class VII and VIII, this is because whenstudents enter the school until the students finish using a curriculum. Thestandard of scores on the minimum completeness criteria (KKM) inschools for the two curriculum is 65. The school has its own policy for theassessment format. The value range for KTSP is the scale of 0-100, whilefor the curriculum 2013 there is a change from a scale of 1-4 to a scale of 0-100. Student report cards for the curriculum 2013 are listed in eachassessment column namely attitude, knowledge and skill, while for KTSPthere is only an attitude assessment, and an assessment of knowledge with skill put together in a single assessment column. Assessment of attitudes in the KTSP report card has been written in it that is the assessment of the personality and noble character of the students filled by teachers with the assessment of the letter, while the attitude assessment in the curriculum 2013 report cards there is a column of assessment of spiritual attitudes and columns assessment of social attitudes that each is still empty, so assessment is filled by the teacher by writing the student's attitude that is seen during the student following the learning process at school.